1965
DOI: 10.1113/expphysiol.1965.sp001783
|View full text |Cite
|
Sign up to set email alerts
|

The Function of the Callosal Connections of the Visual Cortex

Abstract: There is anatomical evidence in cats and baboons of cells at the margin of area 17 which have callosal connections to corresponding points in the opposite hemisphere.The function of such a pathway has been studied in cats after one optic tract has been cut. The corresponding hemisphere now gives early visual responses only at the margin of area 17. Such responses can only be elicited by light stimuli near the vertical meridian of the visual field. These responses are abolished by cooling the corresponding poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
3

Year Published

1968
1968
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(71 citation statements)
references
References 7 publications
7
61
3
Order By: Relevance
“…The fact is that the central margin of the hemifield of one side of the brain projects to that part of the other side which represents the central margin of its hemifield. Choudhury, Whitteridge & Wilson (1965) cut the optic tract on one side in the cat and found that early potentials could be evoked in the lateral edge of area 17 of that hemisphere by light stimuli near the central vertical meridian. These responses were abolished by cutting the callosum or cooling corresponding areas in the other hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…The fact is that the central margin of the hemifield of one side of the brain projects to that part of the other side which represents the central margin of its hemifield. Choudhury, Whitteridge & Wilson (1965) cut the optic tract on one side in the cat and found that early potentials could be evoked in the lateral edge of area 17 of that hemisphere by light stimuli near the central vertical meridian. These responses were abolished by cutting the callosum or cooling corresponding areas in the other hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the callosal connexions at the level of the 17/18 border is currently associated with the necessity of binding together the two halves of the visual field represented separately in the two hemispheres in order to grant perceptual continuity across the vertical meridian and/or to subserve binocular functions such as depth perception (Choudhury, Whitteridge & Wilson, 1965;Hubel & Wiesel, 1967;Berlucchi & Rizzolatti, 1968;Blakemore, 1969Blakemore, , 1970Mitchell & Blakemore, 1970;Berlucchi, 1972; Bishop, 1973; Blakemore, Diao, Pu, Wang & Xiao, 1983;Payne, Pearson & Berman, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…5) and experiments with subjects possessing abnormalities of the visual pathways have established that foveal fine stereoscopy depends upon callosal projections between the two hemispheres (Blakemore, 1969;Mitchell & Blakemore, 1970). Further, the callosal fibres which connect corresponding points in the two hemispheres project, via area 18, to the boundary region between areas 17 and 18 of the monkey visual cortex, the region containing the representation of the vertical meridian in the visual field (Choudhury, Whitteridge & Wilson, 1965). That the suppression effect is restricted to stimuli located around the vertical meridian (Fig.…”
Section: Discussionmentioning
confidence: 99%